INTENTION AND ITS OCCURRENCE IN SPEECH - Najmeddinov Ahmad Rahmatovich (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, the semantic invariant of the category of intentionality consists of a structural set of units representing the judgment “purpose, intention, desire”, which determines the direction of the subject to perform a particular action. The ways of expressing intentionality are varied and varied, which indicates the polycentricity of the scatter of the functional semantic field, that is, that the core-periphery has a differential center.